Odpowiedzi

2009-10-11T14:26:03+02:00
(√10+√2)²= 10 + 2√20 + 2 = 12 + 4√5
(√21+√3)²= 21 + 2√63 + 3 = 24 + 6√7
(√15-√5)²= 15 - 2√75 + 5 = 20 - 10√3
(2√2-√6)²= 8 - 4√12 + 6 = 14 - 8√3
(√21-√20)(√21+√20)= 21 - 20 = 1
1 5 1
2009-10-11T14:28:31+02:00
(a+b)²=a²+2ab+b²

(√10+√2)²=10+2√20+2=12+4√5
(√21+√3)²=21+2√63+3=24+6√7

(a-b)²=a²-2ab+b²

(√15-√5)²=15-2√75+5=20-10√5
(2√2-√6)²=8-4√12+6=14-8√3

(a-b)(a+b)=a²-b²

(√21-√20)(√21+√20)=21-20=1
1 1 1
2009-10-11T14:34:17+02:00
(√10+√2)²= 10 + 2√20 + 2 = 12 + 4√5

(√21+√3)²= 21 + 2√63 + 3 = 24 + 6√7

(√15-√5)²= 15 - 2√75 + 5 = 20 - 10√3

(2√2-√6)²= 8 - 4√12 + 6 = 14 - 8√3

(√21-√20)(√21+√20)= 21 - 20 = 1
1 1 1